PENYELESAIAN PROBLEM HUKUM MELALUI PENDEKATAN MAQASID SHARI’AH - Edi Susilo (Nizham Jurnal Studi Keislaman, 2020)
The Maqasid Shari'ah theory finds its urgency when it is formulated as an alternative to solve various matters related to the formulation of law. Interestingly Maqasid Shari'ah can be transformed in the present context, in the field of law, social and even economic issues, and others. Because indeed the Maqasid Shari'ah theory is formulated to deal with changes, the induction method which is the basis of the theory is the keyword that causes it to be dynamic and can be applied in different contexts. This research is library research. It will explore Maqasid Sharia as a method in istinbath Law. The results of the study are, that Maqasid Shar'iah can be used as an approach in ijtihad to respond to the development of the times by still referring to the al-Qur'an and al-Hadith, by combining particular texts and global intentions. Whereas to find out the Maqasid Shari'ah can be done through istiqra '(taking several samples) for the shari'at applied, and by studying the arguments of the verses of the al-Quran.